Based on Genetic Algorithm to Analyze the Anti-Penetration Properties and Optimize the Structure of Ti-Al3Ti-Al Laminated Composites - Yaoming Li; Huang Zhang; Meini Yuan (Frontiers in Materials, 2022)
A coupled finite-element genetic algorithm technique was used to optimize the arrangement order and layer thickness ratios of Ti-Al3Ti-Al laminated composites. Moreover, the damage evolution, energy conversion, and stress distribution of TC4-Al3Ti-Al laminated composites under impact were analyzed. The results showed that TC4-Al3Ti-Al laminated composites with a layer thickness ratio of 3:14:4 have optimum anti-penetration properties; the projectile kinetic energy is mainly converted into the internal energy of the bullet target system; during the penetration process of TC4-Al3Ti-Al targets, the TC4 layer is shear failure, the Al layer is a petal-like failure, the failure mode of Al3Ti layer is fragmentation; with the number of layer increases, the anti-penetration properties of TC4-Al3Ti-Al targets are gradually increasing. However, when the number of layers is more than 30 layers, the number of layers has little effect on the anti-penetration performance of these composites.